NAVIGATING LEGAL IDENTITY: THE IMPACT OF LEGISLATIVE REFORMS ON TRANSGENDER RECOGNITION AND RIGHTS - Bhatnagar, Astha; Asthana, K. B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines how recent legislative changes have affected transgender rights and recognition, with a particular emphasis on the effects on social inclusion and legal identity. Examining how legislation pertaining to gender identification have changed over time in different jurisdictions, the research shows both progress and enduring difficulties. It looks at how laws might better support transgender people by increasing their legal recognition, preventing discrimination, and facilitating their access to necessary services. The success of these reforms in meeting the demands of the transgender community is also assessed in this report, and gaps where more legislative and policy changes are needed are highlighted. The results highlight the need for comprehensive legal frameworks and ongoing legislative lobbying in order to guarantee equality and safety for transgender individuals.